2022
DOI: 10.3390/md20080466
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Marine Peptides in Prostate Cancer: Mechanistic Insights

Abstract: Prostate cancer (PCa) is the leading cause of cancer death in men, and its treatment is commonly associated with severe adverse effects. Thus, new treatment modalities are required. In this context, natural compounds have been widely explored for their anti-PCa properties. Aquatic organisms contain numerous potential medications. Anticancer peptides are less toxic to normal cells and provide an efficacious treatment approach via multiple mechanisms, including altered cell viability, apoptosis, cell migration/i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 113 publications
(163 reference statements)
0
8
0
Order By: Relevance
“…Using the search terms “prostate cancer” and “marine compounds” in PubMed, an increase in the number of publications on this topic in recent years is apparent ( Figure 3 ). Previous reviews on marine-derived compounds with activities against prostate cancer were focused on specific compound classes, such as active peptides [ 37 ], or were focused on molecules with activities on a range of cancers [ 38 , 39 ], or did not include most recent findings [ 40 ]. The aim of the current review is to summarise recent discoveries of marine compounds with activities against prostate cancer, reporting, when available, the active concentrations and mechanisms of action.…”
Section: Why Marine Organisms and Which Are The Marine-derived Drugs ...mentioning
confidence: 99%
“…Using the search terms “prostate cancer” and “marine compounds” in PubMed, an increase in the number of publications on this topic in recent years is apparent ( Figure 3 ). Previous reviews on marine-derived compounds with activities against prostate cancer were focused on specific compound classes, such as active peptides [ 37 ], or were focused on molecules with activities on a range of cancers [ 38 , 39 ], or did not include most recent findings [ 40 ]. The aim of the current review is to summarise recent discoveries of marine compounds with activities against prostate cancer, reporting, when available, the active concentrations and mechanisms of action.…”
Section: Why Marine Organisms and Which Are The Marine-derived Drugs ...mentioning
confidence: 99%
“…These trials have shown promising results, with some patients experiencing partial or complete responses to treatment and manageable side effects. [13][14][15][16][17] In addition to their anticancer properties, Kahalalides have also been investigated for their potential in other therapeutic areas, including infectious diseases and neurological disorders. For example, Kahalalide F has shown activity against the Zika virus and other flaviviruses, while Kahalalide A has been shown to have neuroprotective effects in animal models of Parkinson's disease.…”
Section: Introductionmentioning
confidence: 99%
“…In preclinical studies, Kahalalides have demonstrated significant anticancer activity against a broad range of tumor types, including breast, lung, colon, and pancreatic cancers. In addition to their direct cytotoxic effects, these compounds have also been shown to have anti‐inflammatory and immunomodulatory properties, further enhancing their potential as cancer therapeutics [13–17] . Several Kahalalide derivatives have been synthesized and evaluated in clinical trials for the treatment of various cancers, including advanced solid tumors and multiple myeloma.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations